Detection of Bacteria in Bladder Mucosa of Adult Females. Issue 5 (19th May 2023) - Wolfe, Alan J.; Rademacher, David J.; Mores, Carine R.; Evans, Robert J.; Overholt, Tyler; Halverson, Thomas; Limeira, Roberto; Matthews, Catherine; Badlani, Gopal; Brubaker, Linda; Walker, Stephen J.
Abstract : Purpose: Interstitial cystitis/bladder pain syndrome is a chronic urological condition diagnosed in nearly 8 million females in the United States. Whether urinary microbiota play an etiological role remains controversial. Most studies assessed the microbiota of interstitial cystitis/bladder pain syndrome patients with voided or catheterized urine as a proxy for bladder urothelium; however, urine may not be a true reflection of the bladder microbiota. Bladder biopsy tissue may provide a more accurate, and thus more clinically relevant, picture of bladder microbiota. Materials and Methods: Bladder biopsy tissues were obtained from: (1) 30 females with interstitial cystitis/bladder pain syndrome (18-80 years old) via cystoscopically guided cold-cup biopsy following therapeutic bladder hydrodistention, and (2) 10 non–interstitial cystitis/bladder pain syndrome females undergoing pelvic organ prolapse repair. To detect bacteria, technical duplicates of each RNAlater-preserved biopsy were subjected to 16S rRNA gene sequencing. To visualize bacteria, paraformaldehyde-fixed, paraffin-embedded biopsies were subjected to a combined multiplexed fluorescence in situ hybridization and fluorescence immunohistochemistry assay and confocal microscopy. Results: Bacteria were detected by 16S rRNA gene sequencing in at least 1 technical duplicate of most biopsies. The most abundant genus was Staphylococcus, followed by Lactobacillus ; Escherichia was common but not abundant. There was no significant difference between interstitial cystitis/bladder pain syndrome patients and controls ( P > .05). Combined fluorescence in situ hybridization and immunohistochemistry reproducibly detected 16S rRNA in epithelial cells and shed cells in the urothelium and lesioned areas and capillary walls in the lamina propria of human bladder biopsy tissue. Conclusions: We conclude that urothelial and urinary microbiota are similar but not identical in adult females.